PERAN STRATEGIS APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DI MASA PANDEMI COVID-19 TINJAUAN DARI PERATURAN PERUNDANG-UNDANGAN: Dibuat oleh Muhaimin (Auditor Madya Inspektorat Kabupaten Pekalongan) - Muhaimin - (Neraca, 2020)
With the outbreak of COVID-19 and having a huge impact on the government, it requires large-scale handling of COVID-19 to prevent the impact of the COVID-19 Pandemic.The tight escort from APIP as the government's internal control.APIP is expected to be able to oversee and ensure government financial accountability in dealing with the COVID-19 pandemic in Indonesia. APIP's strategic role in overseeing the implementation of state / regional financial governance related to refocusing activities, budget reallocation and procurement of goods / services in accelerating the handling of Corona Virus Disease 2019 (COVID-19) including: Reviewing of refocusing and budget reallocation, reviewing of implementation of procurement of goods / services, post audit of goods / services procurement, and giving consultancy / assistance in financial management and procurement of goods / services in handling COVID-19. Keywords : COVID 19, APIP, Refocusing and budget reallocation